2008
DOI: 10.1186/1743-8977-5-17
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary response to intratracheal instillation of ultrafine versus fine titanium dioxide: role of particle surface area

Abstract: Background: The production and use of nanoparticles is growing rapidly due to the unique physical and chemical properties associated with their nano size and large surface area. Since nanoparticles have unique physicochemical properties, their bioactivity upon exposure to workers or consumers is of interest. In this study, the issue of what dose metric (mass dose versus surface area dose) is appropriate for toxicological studies has been addressed. Rats were exposed by intratracheal instillation to various dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
171
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(183 citation statements)
references
References 24 publications
9
171
3
Order By: Relevance
“…This is due to the relatively low lung burdens employed in the present study. For example, Sager et al (2008) reported the dose and time dependence of pulmonary inflammation and lung damage after intratracheal instillation of nano or fine TiO 2 . The rat strain and assay methods used by Sager et al (2008) were identical to those used in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the relatively low lung burdens employed in the present study. For example, Sager et al (2008) reported the dose and time dependence of pulmonary inflammation and lung damage after intratracheal instillation of nano or fine TiO 2 . The rat strain and assay methods used by Sager et al (2008) were identical to those used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sager et al (2008) reported the dose and time dependence of pulmonary inflammation and lung damage after intratracheal instillation of nano or fine TiO 2 . The rat strain and assay methods used by Sager et al (2008) were identical to those used in the present study. The lowest lung burden employed in the Sager et al (2008) study of 260 μg/rat resulted in an 11-fold increase in PMNs harvested by BAL 1 day postexposure.…”
Section: Discussionmentioning
confidence: 99%
“…One of the possible reasons for disagreement is that many studies have been performed using particles with different particle size, surface properties, impurities and crystal structures, involving complex interactions among many factors, and it has been difficult to separate the sole effects of particle size and surface area among many factors. For example, in the research of Bermudez et al 31,32) and Sager et al 35) the TiO 2 nano-and micro-particles used came from different sources and had different crystal structures. Both used the 80% anatase -20% rutile form of TiO 2 particles, generally known by the product name P25, made by Evonik as TiO 2 nanoparticles.…”
Section: Tio 2 Nanoparticlesmentioning
confidence: 99%
“…Both used the 80% anatase -20% rutile form of TiO 2 particles, generally known by the product name P25, made by Evonik as TiO 2 nanoparticles. On the other side, rutile TiO 2 particles produced by DuPont 32) or Sigma Aldrich 35) were used as TiO 2 microparticles. Also, in some studies, measurements of the particles used in the studies were insufficient, making it all the more difficult to validate the nanoparticle paradigm.…”
Section: Tio 2 Nanoparticlesmentioning
confidence: 99%
“…It was thought that TiO 2 -NPs were non-toxic mineral (Sager et al 2008). However, many studies suggested that titanium dioxide nanoparticles could be more toxic than their original materials (Long et al 2007;Zhao Jet al 2009;Zhao Jet al 2011;Magaye and Zhao 2012;Liu K et al 2013).…”
Section: Introductionmentioning
confidence: 99%